Women’s experience of motherhood, violations of supervision requirements and arrests - Adams, Elizabeth A. (The British journal of criminology, 2017)
Though parenting is commonly viewed as an important factor influencing women’s desistance from offending, little is known about how specific aspects of parenting relate to recidivism. The present study investigated the connections of parenting stress, parenting involvement, routine parenting activities and maternal motivations to violations of supervision conditions, including arrests, for a sample of 190 women. The findings support desistance theories that identify involvement in routine prosocial activities, in this case caring for children, as an important explanation for complying with requirements of supervision and avoiding arrest. In contrast, motivations regarding motherhood alone do not appear to provide a strong enough catalyst to shift women away from patterns of lawbreaking.